Quantitative application of fecal sterols using gas chromatography−mass spectrometry to investigate fecal pollution in tropical waters: Western Malaysia and Mekong Delta, Vietnam - Isobe, Kei O.; Tarao, Mitsunori; Zakaria, Mohamad P.; Chiem, Nguyen H.; Minh, Le Y.; Takada, Hideshige (American Chemical Society (ACS), 2002)
This is the first report on fecal pollution using molecular markers in Southeast Asia where serious sewage pollution has occurred. A simple and sensitive analytical method using gas chromatography−mass spectrometry for 10 sterols in various environmental samples was developed to monitor extensive areas of tropical Asia. First, the method was applied to wastewater to confirm that >95% of sterols existed in the particulate phase. Then the approach was applied to a tropical Asian region, Malaysia and Vietnam, with a selection of 59 sampling stations in total. River water and sediment samples were collected and analyzed for chemical markers (coprostanol and other sterols) and microbiological markers (fecal coliforms and fecal streptococci). Particulate coprostanol concentrations ranged from <0.0001 to 13.47 μg/L in tropical river and estuarine waters, indicating severe fecal pollution in populous areas. Coprostanol concentrations in the sediments ranged from 0.005 to 15.5 μg/g-dry. The sedimentary coprostanol concentrations were lower than those reported in some urban areas of industrialized countries. This is probably because frequent heavy rain induces intensive input of eroded soil, which dilutes fecal material in river sediments. The relationship between the concentrations of fecal sterols and bacterial indicators was examined in an attempt to develop public health criteria for coprostanol levels applicable to the tropical region. Coprostanol concentrations of 30−100 ng/L or percent coprostanol levels of 2% corresponded to ∼1000 fecal coliforms per 100 mL, which is set for secondary contact limit in many countries. These coprostanol concentrations were lower than those proposed as criteria in temperate countries, probably owing to greater survival of bacteria in warmer tropical waters. On the basis of these criteria, extensive monitoring of sediments suggests that poor sanitary conditions exist in most of the urbanized area of Malaysia and in several urban and rural sites in Vietnam.